2016
DOI: 10.1111/resp.12762
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin enhances human macrophage control of Mycobacterium tuberculosis infection

Abstract: Background and objective: With the worldwide emergence of highly drug-resistant tuberculosis (TB), novel agents that have direct antimycobacterial effects or that enhance host immunity are urgently needed. Curcumin is a polyphenol responsible for the bright yellow-orange colour of turmeric, a spice derived from the root of the perennial herb Curcuma longa. Curcumin is a potent inducer of apoptosis-an effector mechanism used by macrophages to kill intracellular Mycobacterium tuberculosis (MTB). Methods: An in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 44 publications
1
65
0
1
Order By: Relevance
“…It also reduces the levels of inducible NO synthase, IFN-γ and IL-12 through inhibition of the NF-κB signaling pathway in monocytes/ macrophages (Billerey-Larmonier et al, 2008). In several studies, a significant increase in macrophage phagocytic activity in the presence of curcumin has also been observed (Antony, Kuttan, & Kuttan, 1999;Bai et al, 2016;Mimche, Thompson, Taramelli, & Vivas, 2012;. These studies suggest the potential benefits of curcumin for reducing oxidative and lipid-mediated damages in macrophages (Brouet & Ohshima, 1995;Chan, Huang, Fenton, & Fong, 1998;Kang, Chung, et al, 1999).…”
Section: The Effects Of Curcumin On Neutrophils and Macrophagesmentioning
confidence: 89%
“…It also reduces the levels of inducible NO synthase, IFN-γ and IL-12 through inhibition of the NF-κB signaling pathway in monocytes/ macrophages (Billerey-Larmonier et al, 2008). In several studies, a significant increase in macrophage phagocytic activity in the presence of curcumin has also been observed (Antony, Kuttan, & Kuttan, 1999;Bai et al, 2016;Mimche, Thompson, Taramelli, & Vivas, 2012;. These studies suggest the potential benefits of curcumin for reducing oxidative and lipid-mediated damages in macrophages (Brouet & Ohshima, 1995;Chan, Huang, Fenton, & Fong, 1998;Kang, Chung, et al, 1999).…”
Section: The Effects Of Curcumin On Neutrophils and Macrophagesmentioning
confidence: 89%
“…Curcumin analogs have been reported to show promising in vitro antimycobacterial activity against drug-resistant strains of M.tb (39, 40). Recently, curcumin was shown to augment mycobacterial killing in host macrophages by inducing apoptosis (41). In addition, curcumin potently inhibits hepatotoxicity (38), which is a concurrent problem in many antibiotic therapies that include TB therapy (18).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical studies conducted on some of these ingredients have led to the identification of metabolites such as curcumin, piperine, and capsaicin . Previous pharmacological studies performed on a part of these metabolites revealed, for instance, that curcumin has a large spectrum of bioactivity, including protection from myocardial infarction and the enhancement of human macrophage control of Mycobacterium tuberculosis infection . It also induces apoptosis in upper aerodigestive tract cancer cells, while capsaicin, besides apoptosis, can also induce cell cycle arrest by generating reactive oxygen species .…”
Section: Introductionmentioning
confidence: 99%